Influence of Financial Literacy and Risk Perception on Choice of Investment - Aren, Selim; Zengin, Asiye Nur (ELSEVIER SCIENCE BV, 2016)
During recent years, variables affecting the investment preferences of individual investors are an issue attracting the attention of financial researchers. In this research, we investigate variables which are affecting investment preferences of individual investors. Personality trait is not an important variable, but on the other hand our evidence shows that level of financial literacy and risk perception are important. Besides, risk perception is also affected by financial literacy and gender, but marital status is not effective at the same level. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Financial literacy; Risk perception; Risk appetite; Choice of investment; Bounded Rationality; TOLERANCE; VALUES; GENDER; SCALE; Business & Economics